Incidence and Risk Factors for Systemic Infection in Deceased Donors - (:unkn) unknown (ELSEVIER SCIENCE INC, 2019)
Background. Organ donation shortage is the primary barrier to all organ transplantations.Infectious disease transmission through transplantation is considered controversial for organ retrieval. Donors with bacteremia and sepsis are considered controversial for organ retrieval due to potential transmission of an infectious agent to the recipient. Methods. We retrospectively reviewed the results of bacterial culture of the donor's blood from peripheral venous or central venous catheter, urine, and bronchial aspiration from the organ donation registries of 102 potential donors from the Ministry of Health and Tissue Transplant Coordination Center of Istanbul Region in 2015. Results. Of the 102 deceased donors included in the analysis, 24 (23.5%) had infection. The most common sites of infection were the bloodstream (41.6%) and the respiratory system (37.5%). The most common isolated pathogens of the bacterial cultures were Gram-positive bacteria (21), Gram-negative microorganisms (14), and Candida (1). The significant risk factor for infection was duration of stay at the intensive care unit (median: 5 day; 25-75%: 3-5 day) (odds ratio, 2.94; 95% confidence interval, 1.06-8.12; P < .05). The presence of infection in the donor accounted for a significant part of the reasons why the organs were not accepted for transplantation (kidneys 9%, liver 4%, heart 6%). Conclusions. The study showed that deceased donors with prolonged stays in the intensive care unit have an increased risk for developing nosocomial infections; so there is a need for establishing and enforcing the prevention and control of infection in possible donors.